C-Terminal Lysine Residue of Pneumococcal Triosephosphate Isomerase Contributes to Its Binding to Host Plasminogen - Satoru Hirayama; Takumi Hiyoshi; Yoshihito Yasui; Hisanori Domon; Yutaka Terao (Microorganisms, 2023)
The main causative agent of pneumonia, Streptococcus pneumoniae, is also responsible for invasive diseases. S. pneumoniae recruits human plasminogen for the invasion and colonization of host tissues. We previously discovered that S. pneumoniae triosephosphate isomerase (TpiA), an enzyme involved in intracellular metabolism that is essential for survival, is released extracellularly to bind human plasminogen and facilitate its activation. Epsilon-aminocaproic acid, a lysine analogue, inhibits this binding, suggesting that the lysine residues in TpiA are involved in plasminogen binding. In this study, we generated site-directed mutant recombinants in which the lysine residue in TpiA was replaced with alanine and analyzed their binding activities to human plasminogen. Results from blot analysis, enzyme-linked immunosorbent assay, and surface plasmon resonance assay revealed that the lysine residue at the C-terminus of TpiA is primarily involved in binding to human plasminogen. Furthermore, we found that TpiA binding to plasminogen through its C-terminal lysine residue was required for the promotion of plasmin activation by activating factors.